Chemical synthesis using enzymatically generated building units for construction of the human milk pentasaccharides sialyllacto-N-tetraose and sialyllacto-N-neotetraose epimer - Schmidt, Dirk; Thiem, Joachim (Beilstein Journal of Organic Chemistry, 2010)
α,2-3- and α,2-6-sialylated lactosaminide precursor structures obtained by various enzymatic procedures could be used for glycosylations employing triflic acid/N-iodosuccinimide. Easily accessible selectively protected lactoside derivatives served as acceptor disaccharides to give the corresponding human milk pentasaccharides in good yields. These were characterized by spectroscopic means in the form of their peracetylated derivatives.
Keywords: block synthesis; human milk oligosaccharides; sialyllacto-N-neotetraose epimer; sialyllacto-N-tetraose; trisaccharide thioglycoside donors